Assessment of α-synuclein in submandibular glands of patients with idiopathic rapid-eye-movement sleep behaviour disorder: a case-control study. Issue 7 (June 2016) - Vilas, Dolores; Iranzo, Alex; Tolosa, Eduardo; Aldecoa, Iban; Berenguer, Joan; Vilaseca, Isabel; Martí, Carles; Serradell, Mónica; Lomeña, Francisco; Alós, Llucia; Gaig, Carles; Santamaria, Joan; et al.
Summary: Background: The histological feature of Parkinson's disease is the presence of intraneuronal aggregates of phosphorylated α-synuclein (αSyn). In patients with Parkinson's disease, deposits of αSyn are found in the autonomic nerve fibres of the submandibular gland. Since patients with idiopathic rapid-eye-movement sleep behaviour disorder (IRBD) can develop Parkinson's disease and other synucleinopathies, we investigated whether αSyn deposits could also be detected in their submandibular gland nerve fibres. Methods: We did a case-control study at the Hospital Clinic de Barcelona (Barcelona, Spain) in patients with polysomnographic-confirmed IRBD, patients with clinically diagnosed Parkinson's disease, and controls matched by age with the IRBD group. The controls were either healthy, had had elective neck surgery in the clinic, or were patients who had died in the clinic and had an autopsy. We did a transcutaneous core needle biopsy of the submandibular gland with ultrasound guidance in patients with IRBD or Parkinson's disease, and healthy controls, and without ultrasound guidance in the other controls. We assessed the presence of αSyn with immunohistochemistry using 129-phosphorylated antiserine monoclonal antibody, and analysed quantitative variables with Kruskall-Wallis tests and qualitative variables with Fisher's exact tests. Findings: We did our study between July 16, 2014, and May 16, 2015, and recruited 21 patients with IRBD, 24 patients with Parkinson's disease, and 26 controls (seven healthy, 11 patients undergoing neck surgery, and eight autopsies). We obtained submandibular biopsy material containing glandular parenchyma in nine (43%) of 21 patients with IRBD, 12 (50%) of 24 patients with Parkinson's disease, and all (100%) of the 26 controls. αSyn aggregates were detected in nerve fibres of the glandular parenchyma in eight (89%) of nine patients with IRBD and eight (67%) of 12 with Parkinson's disease, but none of the controls. Of the individuals whose biopsy samples did not contain glandular parenchyma, deposits of αSyn were found in extraglandular tissues in an additional three (25%) of 12 patients with IRBD and five (42%) of 12 patients with Parkinson's disease. None of the controls showed αSyn immunoreactivity in extraglandular tissues. Of the 52 participants who had ultrasonography-guided biopsy, 11 (21%) reported mild-to-moderate local pain, and nine (17%) developed a subcutaneous haematoma; however, these adverse events were transient and did not need treatment. Interpretation: Our findings suggest that, in patients with IRBD, submandibular gland biopsy is a safe procedure for the detection of αSyn aggregates. αSyn detection could be useful for histological confirmation in individuals clinically diagnosed with Parkinson's disease. Funding: Centre for Networked Biomedical Research in Neurodegenerative Disorders (CIBERNED), Barcelona, Spain.